Peranan Pegawai Pencatat Nikah (Ppn) Dalam Mengatasi Perkawinan Di Bawah Umur - Haeran Haeran (Jurnal Al Mujaddid Humaniora, 2020)
Marriage aims to maintain the survival of mankind because marriage means someone has opened a way to preserve their offspring. Before the marriage takes place, it is required to fulfill several conditions including the male has reached the age of 19 years and the woman has reached the age of 16 years. The phenomenon that occurs today is the number of underage marriages. Therefore, one of the serious concerns is the role of the Registrar of Marriage Registration (PPN). This type of research is qualitative research. The approach used is the syar'I juridical approach and the juridical approach. Data collection techniques used were interviews, observation, and documentation. Analysis of the data used is qualitative descriptive analysis. The results of this study were obtained: First, the role of the Registrar of Marriage (PPN) in overcoming underage marriages in Nipah Panjang District, Tanjung Jabung Timur Regency included: (a) As a marriage consultant. It means to resolve conflicts that occur between the parties concerned, including in preventing underage marriages; and (b) the VAT acts as a Marriage Registrar. That is, the PPN supervises the marriage by first checking the requirements and administration of the bride and groom, including age. Second, the obstacles encountered by the Marriage Registrar (PPN) of Nipah Panjang District are: (a) Cultural factors; and (b) the prospective bride has been pregnant first.